2023
DOI: 10.1021/acs.jpcc.3c01017
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Correlations in Aqueous Binary Na+/K+–CH3COO Highly Concentrated Electrolytes

Abstract: Highly concentrated aqueous binary solutions of acetate salts are promising systems for different electrochemical applications, for example, energy storage devices. The very high solubility of CH 3 COOK allows us to obtain water-in-salt electrolyte concentrations, thus reducing ion activity and extending the cathodic stability of an aqueous electrolyte. At the same time, the presence of Li + or Na + makes these solutions compatible with intercalation materials for the development of rechargeable alkaline-ion b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Sodium ion batteries benefit from high natural abundance, low cost, and wide distribution in the Earth’s crust. In the past, various studies have been focused on the utilization of water as a solvent medium in battery electrolytes. These aqueous-based electrolytes are used more widely in supercapacitors, low-cost electronic devices, and grid storage. , Aqueous sodium ion rechargeable batteries are safer and provide nonflammability and high power density with an affordable cost. , The ionic conductivity of lithium ion based aqueous electrolytes is found to be higher than those in organic solvents conventionally used in battery electrolytes. , Dilute aqueous electrolytes suffer from severe drawbacks, including their narrow electrochemical stability window (<1.2 V). , Therein, low voltage causes deposition of water on the electrodes which leads to poor cycling life . In addition, there is a lack of stable solid electrolyte interphase (SEI) formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium ion batteries benefit from high natural abundance, low cost, and wide distribution in the Earth’s crust. In the past, various studies have been focused on the utilization of water as a solvent medium in battery electrolytes. These aqueous-based electrolytes are used more widely in supercapacitors, low-cost electronic devices, and grid storage. , Aqueous sodium ion rechargeable batteries are safer and provide nonflammability and high power density with an affordable cost. , The ionic conductivity of lithium ion based aqueous electrolytes is found to be higher than those in organic solvents conventionally used in battery electrolytes. , Dilute aqueous electrolytes suffer from severe drawbacks, including their narrow electrochemical stability window (<1.2 V). , Therein, low voltage causes deposition of water on the electrodes which leads to poor cycling life . In addition, there is a lack of stable solid electrolyte interphase (SEI) formation .…”
Section: Introductionmentioning
confidence: 99%
“…Further, they compared the solubility and electrochemical performance of different sodium salts dissolved in water and concluded that, apart from having higher salt solubility in water, the anions must involve in the SEI formation to achieve better battery performance. Later on, several research studies on WiSEs emphasized the role of higher salt solubility and the ability of anions to interact with cations in order to enhance the SEI formation as well as suppress the water activity. , In addition to this, in recent studies, various approaches have been adapted to increase the solubility limit of sodium salts in water. ,, The sodium salt having a bis(trifluoromethylsulfonyl)imide (TFSI) anion has a limited solubility of around 7 m in water, but it shows a dense SEI formation at a lower salt concentration as compared to LiTFSI salt . Also, sodium bis(fluorosulfonyl)imide (NaFSI) based aqueous electrolyte renders its electrochemical potential window up to 2.6 V at a high salt concentration of 35 m .…”
Section: Introductionmentioning
confidence: 99%
“…The hydration of ions significantly influences the electrochemical stability window of aqueous electrolytes to a large extent. 41 Raman spectroscopy and Fourier transform infrared (FTIR) spectroscopy were employed in this work to elucidate the hydrogen-bonding networks in LiNO 3 aqueous solutions. It should be noted that these solubility values represent the solubility limits of stable supersaturated solutions prepared by dissolving LiNO 3 at 35 °C and then cooling the solution to room temperature, as described in the literature.…”
mentioning
confidence: 99%
“…The hydration of ions significantly influences the electrochemical stability window of aqueous electrolytes to a large extent . Raman spectroscopy and Fourier transform infrared (FTIR) spectroscopy were employed in this work to elucidate the hydrogen-bonding networks in LiNO 3 aqueous solutions.…”
mentioning
confidence: 99%